2000
DOI: 10.1016/s0006-3495(00)76740-3
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin Interfacial Behavior: The Impact of Changing Acyl Chain Composition

Abstract: Sphingomyelins (SMs) containing homogeneous acyl chains with 12, 14, 16, 18, 24, or 26 carbons were synthesized and characterized using an automated Langmuir-type film balance. Surface pressure was monitored as a function of lipid molecular area at constant temperatures between 10 degrees C and 30 degrees C. SM containing lauroyl (12:0) acyl chains displayed only liquid-expanded behavior. Increasing the length of the saturated acyl chain (e.g., 14:0, 16:0, or 18:0) resulted in liquid-expanded to condensed two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
88
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 63 publications
(95 reference statements)
18
88
1
Order By: Relevance
“…Two structural features of SM that enable it to provide a specialized membrane environment with a tendency to form microdomains are the presence 1) at the membrane surface of functional groups capable of functioning as donors (the hydroxyl group) and acceptors (the nitrogen in the amide bond) in hydrogen bond interactions with neighboring lipids and 2) deeply embedded in the membrane, of hydrophobic chains with marked length asymmetry (26,27). By comparing the behavior in monolayers of pure SM with medium (C12-C14), long (C16 -C18), and very long (C24 -C26) acyl chains, it was shown that chain length alone has an important impact on interfacial properties (26).…”
Section: Discussionmentioning
confidence: 99%
“…Two structural features of SM that enable it to provide a specialized membrane environment with a tendency to form microdomains are the presence 1) at the membrane surface of functional groups capable of functioning as donors (the hydroxyl group) and acceptors (the nitrogen in the amide bond) in hydrogen bond interactions with neighboring lipids and 2) deeply embedded in the membrane, of hydrophobic chains with marked length asymmetry (26,27). By comparing the behavior in monolayers of pure SM with medium (C12-C14), long (C16 -C18), and very long (C24 -C26) acyl chains, it was shown that chain length alone has an important impact on interfacial properties (26).…”
Section: Discussionmentioning
confidence: 99%
“…5D ) of the fl uorescence melting temperature SLs. The strong asymmetry of VLCSLs might also affect the packing and the distribution of the bulk lipids in the bilayer by promoting the formation of interdigitated phases ( 19,20,(40)(41)(42).…”
Section: Effect Of Cer Acyl Chain Structure On Membrane Biophysical Pmentioning
confidence: 99%
“…Considering this hypothesis, the enrichment in VLC-SLs in CerS2-transfected cells might contribute to the formation of membrane regions enriched in these VLC-lipids that tend to segregate from other lipid components as a consequence of the strong mismatch between their chain structures, and therefore cause an increase in the fraction of ordered membrane regions. In addition, VLC-SLs have higher melting temperatures compared with LC-SLs [e.g., ( 40 )], which contributes to a decrease in their miscibility with the other lipid components and consequent formation of more ordered membrane regions enriched in these high differences were observed, which can be explained by the formation of different acyl chain Cers in the PM. Accordingly, these results suggest that alterations in SL metabolism by transfecting cells with different CerSs leads to a change in the lipid composition of the PM, most likely due to the changes introduced in the acyl chain structure of the SL formed.…”
Section: Cer-induced Membrane Remodelingmentioning
confidence: 99%
“…7). MD simulations and monolayer experiments [15][16][17] suggest that only the SM species with a suitable dynamic volume would fit into the cavity of the p24 TMD formed by V13, T16, and L17, excluding lipids with larger dynamic volume (SM 14 and 16, see Supplementary Fig. 7).…”
mentioning
confidence: 99%